Altered subthalamo-pallidal synchronisation in parkinsonian dyskinesias. Issue 3 (16th February 2005) - Foffani, G; Ardolino, G; Meda, B; Egidi, M; Rampini, P; Caputo, E; Baselli, G; Priori, A
Abstract : The aim of this work was to study the role of subthalamo-pallidal synchronisation in the pathophysiology of dyskinesias. We recorded local field potentials (LFPs) in a patient with Parkinson's disease and left surgery induced dyskinesias with double, bilateral deep brain stimulation electrode implants in the subthalamic nucleus (STN) and the globus pallidus internus (GPi). Synchronisation was studied through coherence analysis. In the nuclei contralateral to the dyskinetic side of the body there was decreased STN-GPi coherence in the high beta range (20–30 Hz) and an enhanced coherence at low frequencies (<10 Hz). Despite the possible limitations arising from single-case observations, our findings suggest that parkinsonian dyskinesias are related to altered synchronisation between different structures of the basal ganglia. Firing abnormalities within individual basal ganglia nuclei are probably not enough to account for the complex balance between hypokinetic and hyperkinetic symptoms in human parkinsonian dyskinesias and altered interactions between nuclei should also be considered.